Understanding mechanism of performance improvement in nitrogen-doped niobium superconducting radio frequency cavity. Issue 2 (1st February 2023) - Fang, Xiaotian; Oh, Jin-Su; Kramer, Matt; Romanenko, A.; Grassellino, A.; Zasadzinski, John; Zhou, Lin
ABSTRACT: Niobium superconducting radiofrequency cavities enable applications in modern accelerators and quantum computers. However, the surface resistance significantly deteriorates the cavities' performance. Nitrogen doping surface treatment can consistently increase cavity performance by reducing surface resistance, but the improvement mechanism is not fully understood. Herein, we employed transmission electron microscopy and spectroscopy to uncover the structural and chemical differences of the Nb/air interface between the non-doped and nitrogen-doped cavities. The results indicate that nitrogen doping passivates the Nb surface by introducing a compressive stress/strain close to the Nb/air interface, which impedes the diffusion of oxygen and hydrogen atoms and reduces surface oxide thickness. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: A comprehensive structural and chemical study of the Nb/air interface from the non-doped and nitrogen-doped niobium cavity helps to understand the performance improvement mechanisms of the nitrogen-doped cavity.